Peptide nucleic acid (PNA) clamps reduce amplification of host chloroplast and mitochondria rRNA gene sequences and increase detected diversity in 16S rRNA gene profiling analysis of oak-associated microbiota - Usman Hussain; Jim Downie; Amy Ellison; Sandra Denman; James McDonald; Marine C. Cambon (Environmental Microbiome)
Abstract Background Acquiring representative bacterial 16S rRNA gene community profiles in plant microbiome studies can be challenging due to the excessive co-amplification of host chloroplast and mitochondrial rRNA gene sequences that reduce counts of plant-associated bacterial sequences. Peptide Nucleic Acid (PNA) clamps prevent this by blocking PCR primer binding or binding within the amplified region of non-target DNA to stop the function of DNA polymerase. Here, we applied a universal chloroplast (p)PNA clamp and a newly designed mitochondria (m)PNA clamp to minimise host chloroplast and mitochondria amplification in 16S rRNA gene amplicon profiles of leaf, bark and root tissue of two oak species (Quercus robur and Q. petraea). Results Adding PNA clamps to PCR led to an overall reduction of host chloroplast and mitochondrial 16S rRNA gene sequences of 79%, 46% and 99% in leaf, bark and root tissues, respectively. This resulted in an average increase in bacterial sequencing reads of 72%, 35%, and 17% in leaf, bark, and root tissue, respectively. Moreover, the bacterial diversity in the leaf and bark increased, with the number of ASVs rising by 105 in the leaf samples and 218 in the bark samples, respectively. In root tissues, where host oak chloroplast and mitochondria contamination were low, alpha and beta diversity did not change, suggesting the PNA clamps did not bias the bacterial community. Conclusion In conclusion, this study shows that PNA clamps can effectively reduce host chloroplast and mitochondria PCR amplification and improve assessment of the detected bacterial diversity in Quercus petraea and Quercus robur bacterial 16S rRNA gene sequencing studies.